(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Cholpon’s work “Night and Day” is notable for its vivid description of the author’s aesthetic taste and worldview. This article consists of the author’s general opinions about the heroes of the novel. In the novel, Zebi is depicted as an obedient, simple symbol of the Uzbek woman of the last century, Mingbashi is a mischievous man, Miryoqub is cunning, and Jadidchi is a man bringing news.